MODERNTECHNIQUE IN CONSTRUCTION PROJECT MANAGEMENT - Ismael A. J. Al-Mashhadani (Journals Park Publishing, 2022)
In project management, resource types, and other business practices increase, RCSP issues become more important. Thus, recent research has focused on metaphysics or evolutionary algorithms, mainly genetics (GA), and these methods include the work of. Martínez-Rojas, Marín and Vila (2016) recently developed a two-step genetic algorithm that also took into account litigation and resource constraints. To maximise these two objectives together, two subsystems were developed and implemented in parallel. One of the biggest challenges for project management is a limited resource plan. This is a merger optimisation problem with many contradictory goals and limitations, that is, limiting the daily use of resources within available resources, completing the project as soon as possible and manage your daily resources in the most coordinated way possible (Faghihi et al., 2015). Also, there are reports on time and cost savings, better communication and coordination, quality improvements, negative risk reduction, scope explanation, better organisation, reduction of software problems, reduction of knowledge growth and reduction of design costs and outsourcing.
Keywords: project; management; resource